Validity and reliability of the Japanese version of the Patient Satisfaction Questionnaire (PSQ-J) for evaluating oncologist consultations - Yuiko Kamo; Maiko Fujimori; Mariko Asai; Takayuki Oishi; Masanori Mori; Mitsunori Miyashita; Tatsuya Morita; Yosuke Uchitomi (Elsevier, 2023)
Objective: To develop the Japanese version of the Patient Satisfaction Questionnaire (PSQ-J) and examine its validity and reliability. Methods: A cross-sectional, web-based survey was conducted among cancer patients in Japan. The PSQ-J was developed following the forward-backward translation method, using a numerical rating scale. Data on patient characteristics and psychometric scales, like the PSQ-J, willingness to recommend an oncologist to others, trust in the healthcare system, uncertainty, and the Physician Compassion Questionnaire were collected. Validity was examined using exploratory and confirmatory factor analyses and by calculating the correlations between the total PSQ-J score and the criterion variables. Reliability was confirmed by Cronbach's alpha and test-retest score correlations at a two-week interval. Results: The first and second surveys were conducted on 309 and 107 patients, respectively. One-dimensionality and model fit were verified using factor analyses. The PSQ-J was significantly associated with other comparable scales. Cronbach's alpha was 0.962; the correlation between the PSQ-J test-retest scores was 0.835 (p < .001). Conclusion: The current study indicates that the PSQ-J can be valid and reliable for assessing satisfaction with oncologist consultation. Innovation: The PSQ-J enables the effective assessment of patient satisfaction with oncologist consultations, leading to better practice reflecting the patient's viewpoint.